Effect of dietary fat on adipocyte size in farmed age‐2 white sturgeon (Acipenser transmontanus, Richardson, 1836). (12th December 2017) - Treanor, H. B.; Miller, I. R.; Halvorson, L. J.; Van Eenennaam, J. P.; Doroshov, S. I.; Webb, M. A. H.
Summary: Determining the age at which farmed sturgeon begin storing ovarian fat will potentially enable sturgeon farmers to adjust husbandry practices, such as feeding different dietary fat levels at an early age. We investigated the influence of dietary fat on the size of ovarian adipocytes in farmed age‐2 white sturgeon Acipenser transmontanus . At age 1 month, all fish were fed a commercial high fat (HF; 17% fat) diet. At age 6 months, half were transitioned to an experimental low fat (LF; 9% fat) diet. Fish at this time averaged 160 g (±30 g), and individual tank density was 4.1 kg/m 3 . Tanks were 3.7 m in diameter, 1.3 m deep, each with a volume of 13.7 m 3 . Each tank maintained a flow rate of 150 L/min using groundwater with water temperatures ranging from 19 to 21°C and dissolved oxygen ranging from 6.5 to 12.0 ppm. All fish were fed the diet assigned to their tank for an additional 18 months prior to sampling. At age 25 months (now referred to as "age 2"), tissue was collected from fish and processed histologically. Adipocytes were measured along the ovarian fold (anterior), furthest from the ovarian fold (posterior), and randomly in between the anterior and posterior sections. Randomly chosen adipocytes from each location were measured histologically. Mean adipocyte size did not statistically differ among sample locations in fish fed the same diet. Once pooled by sampling location, average adipocyte size was 5, 491.18 μm (±98.97) in fish fed the HF diet and 3, 348.62 μm (±40.85) in fish fed the LF diet. Fish fed the HF diet had larger adipocytes than fish fed the LF diets ( t = 20.01, df = 78.54, p < .01). The results demonstrate that diet can influence the size of adipocytes found in juvenile white sturgeon ovaries. Additional research is needed to determine whether the accumulation of large adipocytes as a juvenile confers to adulthood and influences reproductive ability and caviar yield and quality.